New giant penguin bones from Antarctica: Systematic and paleobiological significance - Acosta Hospitaleche, Carolina Ileana Alicia (2014)
A tarsometatarsus and a fragmented humerus of striking dimensions recently collected in the Late Eocene locality DPV 13/84 Submeseta Formation-level 38 Submeseta II-, Seymour (Marambio) Island, Antarctic Peninsula were both assigned to Palaeeudyptes klekowskii. According to estimates, the tarsometatarsus would belong to the largest and most massive penguin described so far. This bird was probably a piscivorous penguin, with high diving ability for catching prey. Although the humerus is not an appropriate element for body mass or body length assessments, it also belonged to a huge penguin.